Amina Wadud: Pendekatan Hermeneutika Untuk Gerakan Gender - Amin, Muhammad Fahrizal (AL-ADYAN, 2020)
Islam is a religon that very upholds of prestige and dignity every person without discriminate of gender, both men and women. However, as time goes by, the sculpture of religion becomes multi-commentation for praising certain gender and humiliating others. The gender inequality of social role is considered as divine creation, it means that everything comes from God. In contrast to the perception of feminist who considers the inequality as a social construction. The gender inequality of social role is still retaining under excuse of religion doctrine. Religion is involved to preserve conditions in which women do not consider themselves equal to men. It is possible that behind of this theological "consciousness" occurs anthropological manipulation that aims to establish a patriarchal structure, which generally harms women and benefits only certain classes of society. Looking at this paradigm shift, Amina Wadud is trying to boost the understanding that has deviated far from the Al Qur'an award on women.